Plant–Pathogen Maneuvering over Apoplastic Sugars. (September 2017) - Naseem, Muhammad; Kunz, Meik; Dandekar, Thomas
Abstract : The nutrient-rich extracellular plant compartment, the apoplast, is an attractive niche for attacks by microbial pathogens. Here, we highlight recent trends in plant–pathogen competition for apoplastic sugars in the context of innate immune responses in various plant–pathogen interaction systems.